Strategies for Strengthening Civic Responsibility Among Students Through Pancasila and Civic Education - Anjulin Yonathan Kamlasi; Taufiqurrahman Taufiqurrahman; Fredik Lambertus Kollo; Thomas Kemil Masi; Melinda Ratu Radja; Tri Utami (Sakura Digital Nusantara, 2026)
Strengthening civic responsibility is one of the important objectives of civic education in higher education, particularly in shaping students as active, participatory, and responsible citizens in democratic life. This study aims to analyse strategies for strengthening students' civic responsibility through Civic Education learning in the Pancasila and Civic Education Study Programme, Faculty of Teacher Training and Education, Nusa Cendana University. The research uses a qualitative approach. The research informants consist of lecturers teaching Civic Education courses and students of the Civic Education Study Programme, Faculty of Teacher Training and Education, Nusa Cendana University, who were selected purposively. Research data were collected through in-depth interviews, observation of the learning process, and analysis of documentation in the form of Semester Learning Plans (RPS), teaching materials, and student academic activities. Data analysis techniques used data reduction, data presentation, and conclusion drawing techniques. The results of the study show that several key strategies in strengthening civic responsibility for students through Civic Education are project-based learning, integrated service learning, deliberative pedagogy (structured discussions, debates, and simulated public forums), strengthening the role of student organisations and practical leadership, as well as digital literacy and the use of media for civic participation (digital citizenship). Strengthening civic responsibility through PPKn must be integrative, contextual, and sustainable with adequate institutional support, facilities, and habits in campus and community life. This research contributes scientifically to the development of civic education studies in higher education by offering a conceptual model for strengthening student civic responsibility based on an integrative PPKn learning strategy that combines classroom learning, social experiences, and digital participation. The findings of this study also enrich the literature on relevant civic pedagogy practices to strengthen students' civic competencies in facing contemporary democratic challenges.